G79(P) What is the value of paediatric assessment in historic child sexual abuse?. (24th May 2017) - Al-Jilaihawi, S; Borg, K; Maguire, S; Hodes, D
Abstract : Introduction: There is a perception that there are few benefits of a paediatric assessment in historic child sexual abuse (CSA), as the likelihood of finding forensic evidence is low. Aim: To determine the value of a comprehensive paediatric assessment in a dedicated clinic for children and young people who present following suspicion or allegation of historic CSA. Method: All children with suspected or alleged historic CSA, defined as >7 days after the last episode of sexual assault in pubertal girls, or >3 days for pre-pubertal girls and all boys, were assessed in a specialised paediatric clinic. Clinic data was collected prospectively between October 2009 and November 2014 and through retrospective case note review. Results: 249 children presented with possible historic CSA, ranging from one week to one year after the episode. Ages ranged from 0–17 years, median 7 years, standard deviation 4.3. Indications for referral varied significantly with age (p<0.001). Of these children, 141 (57%) had a medical concern(s) related to the referral reason, 78 (31%) had an unrelated medical concern(s) and 55 (22%) had emotional or behavioural concerns requiring onward referral (Table 1 ). Furthermore, 18 (7%) children had physical signs supportive of CSA, significantly associated with alleged penetration (p<0.001). Findings referable to Social Care were identified in 26 cases (10%), the police in 6 cases, and 15 (6%) parents required professional help for anxiety symptoms. Conclusion: This study highlights the value of a comprehensive paediatric assessment in a dedicated clinic for cases of suspected or alleged historic CSA, by identifying a broad variety of unmet health needs in this vulnerable group. These findings have important implications for the child, their families, and the multiagency team.